1994
DOI: 10.1073/pnas.91.3.1019
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ethanol on cytochrome P450 in the rat brain.

Abstract: After a single dose of ethanol (0.8 ml/kg) administered intraperitoneally, the P450 content of the rat brain increased from 62 + 19 to 230 ± 97 pmol/g (wet weight) of tissue (mean ± SD, n = 5). Most of this increase could be accounted for by a 10-to 20-fold increase in the olfactory lobes and hypothalamic preoptic area. The P450s were identified by Western blot analysis and by microsequencing of the N-terminal ends after resolution of the proteins on SDS gels. They were identified as P450 2C7, 2C11, 2E1, 4A3, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
0
3

Year Published

1997
1997
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(77 citation statements)
references
References 41 publications
1
73
0
3
Order By: Relevance
“…Ethanol is metabolized to acetaldehyde mainly by the alcohol dehydrogenase pathway both peripherally and in the brain (Raskin and Sokoloff 1970) and, to a lesser extent, by oxidation through the microsomal inducible isoenzyme CYP2D1 (Warner and Gustafsson 1994) and the catalase-H 2 O 2 system (Aragon et al 1992). Acetaldehyde is subsequently transformed to acetate by aldehyde dehydrogenase.…”
Section: Discussionmentioning
confidence: 99%
“…Ethanol is metabolized to acetaldehyde mainly by the alcohol dehydrogenase pathway both peripherally and in the brain (Raskin and Sokoloff 1970) and, to a lesser extent, by oxidation through the microsomal inducible isoenzyme CYP2D1 (Warner and Gustafsson 1994) and the catalase-H 2 O 2 system (Aragon et al 1992). Acetaldehyde is subsequently transformed to acetate by aldehyde dehydrogenase.…”
Section: Discussionmentioning
confidence: 99%
“…The appearance of multiple forms of P450 in brain and their selective inducibility by a variety of drugs and xenobiotics have also been identified (9,(12)(13)(14). CYP2D is one of the major forms of P450 present in both rat (15) and human brain (16).…”
mentioning
confidence: 99%
“…First of all, the role of ADH in the brain ethanol metabolism remains unclear, since although the presence of brain ADH has been observed, it has been reported that ethanol is not a good substrate in this organ (Beisswenger et al, 1985;Kerr et al, 1989). Other studies have shown an increase in cytochrome P450 in the brains of rats treated with ethanol (Warner & Gustafsson, 1994), observing induction of nerve cells and support cells due to the action of ethanol in the cerebellum, cerebral cortex, thalamus and hippocampus (Sohda et al, 1993;Tindberg & Ingelman-Sundberg, 1996;Upadhya et al, 2000). Additionally, Zimatkin et al (2006) reinforced in rats and mice the possibility that cytochrome P450 is involved in the brain ethanol metabolism.…”
Section: Introductionmentioning
confidence: 97%